Synthesis and Characterization of Graphene Oxide-Based Composite Membranes for Enhanced Seawater Desalination Process Efficiency - Andi Haslinah; Lieza Corsita; Setiarto Pratigto; Indah Tri Rizky; Adianti Putri Alitonang (Science Journal Get Press, 2026)
Graphene oxide (GO) is a promising nanomaterial for membrane-based desalination due to its tunable interlayer structure and abundant surface functionalities. This study synthesized and characterized a graphene oxide titanium dioxide (GO–TiO₂) composite membrane via vacuum-assisted filtration to enhance seawater desalination performance. Characterization using XRD, FTIR, SEM, and contact angle analysis confirmed uniform TiO₂ incorporation, which expanded GO interlayer spacing from 0.77 nm to 0.90 nm, increased hydrophilicity, and improved structural stability. Forward osmosis (FO) tests using 3.5 wt% NaCl feed solution showed that the GO–TiO₂ membrane achieved over 99% salt rejection and a 125% increase in water flux compared to pristine GO membranes. TiO₂ acted as a nano-spacer and hydrophilic agent, reducing GO restacking and facilitating water transport. These results indicate that the GO–TiO₂ composite membrane offers enhanced permeability, selectivity, and durability, making it a promising candidate for sustainable seawater desalination.